2017
DOI: 10.1177/0040517517705628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contact method and acclimation on temperature and humidity in touch perception

Abstract: Physical stimuli from contacted objects are recorded by skin receptors and are transmitted to neural signals to the cerebrum to generate touch perceptions. Despite numerous studies having been conducted on the link between the physical properties of contacted objects and psychological sensations, factors besides the stimuli themselves have seldom been investigated. The contact method and acclimation to environmental factors, such as temperature and humidity, could affect the functions of responsible receptors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 51 publications
0
20
1
Order By: Relevance
“…31 Smoothness refers to a surface free from projections, irregularities or inequalities. 32 The opposite property of smoothness is roughness which is described by the indentations and ridges on the fabric surface. 33 Softness relates to the ability of the fabric to bend as fabrics that can easily bend are described as soft and the opposite property is stiff or hard.…”
Section: Blind Rating Methods Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Smoothness refers to a surface free from projections, irregularities or inequalities. 32 The opposite property of smoothness is roughness which is described by the indentations and ridges on the fabric surface. 33 Softness relates to the ability of the fabric to bend as fabrics that can easily bend are described as soft and the opposite property is stiff or hard.…”
Section: Blind Rating Methods Experimental Proceduresmentioning
confidence: 99%
“…These three attributes are often used to explain the judgements made on fabric handle 9,30 and also included in ASTM D123 standards on terminology used to describe hand. 31 Smoothness refers to a surface free from projections, irregularities or inequalities 32 . The opposite property of smoothness is roughness which is described by the indentations and ridges on the fabric surface 33 .…”
Section: Sample Preparation and Handlingmentioning
confidence: 99%
“…In particular, at the starting point of the ''touching task'' block, one piece of fabric (10 cm Ă‚ 10 cm) was put into the interspace between the thumb and index finger of the subject's right hand, and the subject was required to perform the task of touching the fabric for 30 seconds. Because the touch sensations can be affected by the contact method, 31 the subjects were required to touch the fabric in a specified way. Before the formal experiment, a piece of light cotton fabric was used to train all the subjects touching the fabric in the same way as follows: the subjects were required to gently hold (or pinch) the fabric with small pressure just using the thumbs and index fingers of their right hands, and then repeatedly rotate and rub the thumbs on the fabric surface in the anti-clockwise direction, at the frequency of about 1 Hz for 30 seconds, to consciously feel the touch feeling of the fabric.…”
Section: Fmri Experimentsmentioning
confidence: 99%
“…Related studies 30 have shown that the method of active touch is able to generate more physical stimuli than passive touch, as it involves the exertive manipulating of objects. 31 Therefore, subjects in this study were required to touch fabrics in active methods, rather than receiving fabric touch passively.…”
mentioning
confidence: 99%
“…Liao et al. 2 and Simões-Franklin et al. 5 evaluated fabric texture using two methods of contact on the arm and forearm, namely passive touch and active touch.…”
mentioning
confidence: 99%